2020
DOI: 10.1002/ange.201915034
|View full text |Cite
|
Sign up to set email alerts
|

A Supported Bismuth Halide Perovskite Photocatalyst for Selective Aliphatic and Aromatic C–H Bond Activation

Abstract: Direct selective oxidation of hydrocarbons to oxygenates by O2 is challenging. Catalysts are limited by the low activity and narrow application scope, and the main focus is on active C−H bonds at benzylic positions. In this work, stable, lead‐free, Cs3Bi2Br9 halide perovskites are integrated within the pore channels of mesoporous SBA‐15 silica and demonstrate their photocatalytic potentials for C−H bond activation. The composite photocatalysts can effectively oxidize hydrocarbons (C5 to C16 including aromatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 88 publications
2
40
0
Order By: Relevance
“…Again, no induction period was observed and the reaction presented essentially the same kinetic profile as those observed in the presence of BiBr 3 . These results strongly support that Bi 2 O 3 acts as a pre-catalyst and its interaction with bromo-derivatives lead to the formation of a soluble Bi n Br m -species triggering the photocatalytic process 39 .…”
Section: Resultssupporting
confidence: 69%
“…Again, no induction period was observed and the reaction presented essentially the same kinetic profile as those observed in the presence of BiBr 3 . These results strongly support that Bi 2 O 3 acts as a pre-catalyst and its interaction with bromo-derivatives lead to the formation of a soluble Bi n Br m -species triggering the photocatalytic process 39 .…”
Section: Resultssupporting
confidence: 69%
“…Lead‐free Cs 3 Bi 2 Br 9 perovskite was reported as photocatalyst for solar‐driven organic synthesis of epoxide alcoholysis, 146 where the Lewis‐acid sites on the Cs 3 Bi 2 Br 9 surface play a vital role in activation of the epoxide (Figure 6H). In addition, the strong interactions between aromatics and Cs 3 Bi 2 Br 9 with Bi atoms as Lewis‐acid sites were also observed in the photocatalytic oxidation of toluene 142 . Therefore, it appears that the Bi‐based halide perovskites seem to have a satisfactory catalytic effect on reactions requiring Lewis‐acid activation.…”
Section: Photoelectric Applications Of Halide Perovskitesmentioning
confidence: 96%
“…Halide perovskites present potential in photocatalytic synthesizing of valuable organic compounds thanks to their excellent photoelectric properties. It has been reported that halide perovskites can be employed for photocatalytic selective oxidation of benzyl alcohols, 139,140 activate C(sp3)‐H bond, 141,142 CC bond cleavage and dehydrogenation catalysis, CC, CO, and CN bond formations, 143‐145 and ring‐opening reactions of epoxides and so on 146 . For example, halide perovskite CsPbBr 3 /TiO 2 composite has been used to photo‐oxidize benzyl alcohol to benzaldehyde under visible‐light illumination (Figure 6A,B).…”
Section: Photoelectric Applications Of Halide Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, halide perovskites can be solution processed at low temperatures, which significantly reduces their fabrication cost and complexity 4 . These advantages have led to the emergence of a variety of novel perovskite-based devices in the past decade 5 , 6 , such as solar cells (SCs) 7 – 10 , light-emitting diodes (LEDs) 11 14 , lasers 15 17 , photodetectors (PDs) 18 20 , sensors 21 , 22 , catalyst electrodes 23 25 , field-effect transistors 26 , 27 , fuel cells 28 , 29 , memory 30 , 31 and spintronic devices 32 , 33 . However, halide perovskites are prone to phase changes and compositional degradation in the ambient environment.…”
Section: Introductionmentioning
confidence: 99%